INSPECTION SYSTEM, PROGRAM, AND THE LIKE - KOBAYASHI NORIHISA; NAKAI YASUTO; NAKASHIOYA TSUKASA; TAKAHASHI KEIZO; SHIMIZU YUKI; HIGASHIYAMA TAKUYA; OSHIMA HIROAKI (2024)
To provide a system that is better than a conventional system, such as easily performing multiple inspection items to be executed to inspected objects in order.SOLUTION: An inspection system for inspecting at least one inspection object successively executes multiple inspection items to an object to be inspected. As one example, multiple devices (for example, horns 150 to 157) used for multiple inspection items are arranged, and the respective devices start operating by moving inspected objects to positions that oppose the respective devices. As another example, the inspection system includes a function of generating and displaying an inspection screen showing inspected objects and multiple inspection items and a function of successively executing multiple inspection items displayed on the inspection screen on the basis of an inspection definition file corresponding to one inspection object from among previously created multiple inspection definition files corresponding to respective inspection objects that specify inspected objects and multiple inspection items for multiple inspection objects.SELECTED DRAWING: Figure 1 【課題】検査する物へ順番に実行させる複数の検査項目を容易に行うなど、従来よりも優れたシステムを提供すること。【解決手段】少なくとも一つの検査対象を検査する検査システムであって、検査対象となる検査する物へ、複数の検査項目を順次実行させる。一例として、複数の検査項目に用いる複数の機器（例えば、ホーン１５０～１５７）を配列し、検査する物を各機器と対向する位置に移動させることにより、各機器が動作を開始する構成とする。他の例として、複数の検査対象について、検査する物と複数の検査項目とを特定する、予め作成された各検査対象に対応する複数の検査定義ファイルのうち、一つの検査対象に対応する検査定義ファイルに基づいて、検査する物と複数の検査項目とを示す検査用画面を生成して表示する機能と、検査用画面に表示された複数の検査項目を順次実行させる機能とを備える構成とする。【選択図】図１